PERAN AUDIT RISK DAN AUDIT EFFORT MEMEDIASI HUBUNGAN ANTARA WOMEN IN AUDIT COMMITTEE DAN BIAYA AUDIT - Azizah , Mardiana; zaitul, Zaitul; Mawardi, Herawati; Ilona, Desi (Politeknik Negeri Ambon, 2023)
The role of audit risk and audit effort as mediating variable between women in audit committee and audit fee has rarely been investigated using Indonesia data. Therefore, this study develops this complex relationship model using services companies from 2016-2018 periods. The final sample is 88 companies due to not all companies disclose their audit fee data. the result indicates that there is no direct effect of women in audit committee on audit fee, audit risk and audit effort. In addition, the audit risk significantly influences the audit fee, but not for audit effort. Further, the role of audit risk and audit effort as mediating variables between women in audit committee are not evidenced. However, control variables partially have a direct relationship with audit fee.